2021
DOI: 10.1094/phyto-07-20-0292-r
|View full text |Cite
|
Sign up to set email alerts
|

A Putative MAPK Kinase Kinase GeneSsos4is Involved in Mycelial Growth, Virulence, Osmotic Adaptation, and Sensitivity to Fludioxonil and is Essential for SsHog1 Phosphorylation inSclerotinia sclerotiorum

Abstract: The high osmolarity glycerol (HOG) pathway, comprising a two-component system and the Hog1 MAPK cascade, plays a pivotal role in eukaryotic organisms. Previous studies suggested that the biological functions of some key genes in the HOG pathway varied in filamentous fungi. In this study, we characterized a putative mitogen activated kinase (MAPK) kinase kinase gene Ssos4 in S. sclerotiorum, which encoded a phosphotransferase in the MAPK cascade. Compared to the wild-type progenitor HA61, the deletion mutant ∆S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…For example, knocking out Sak1 in the B. cinerea high osmolarity pathway abolished compound appressoria formation required for host entry (Segmüller et al, 2007). Similarly in S. sclerotiorum , disruption of the osmolarity responsive MAPKKK Ssos4 led to reduced sclerotia formation and virulence (Li et al, 2021). Deletion of the cell wall integrity MAPK cascade components not only led to decreased cell wall integrity, but also decreased sclerotia formation and virulence (Bashi et al, 2016; Cong et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, knocking out Sak1 in the B. cinerea high osmolarity pathway abolished compound appressoria formation required for host entry (Segmüller et al, 2007). Similarly in S. sclerotiorum , disruption of the osmolarity responsive MAPKKK Ssos4 led to reduced sclerotia formation and virulence (Li et al, 2021). Deletion of the cell wall integrity MAPK cascade components not only led to decreased cell wall integrity, but also decreased sclerotia formation and virulence (Bashi et al, 2016; Cong et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of the cell wall integrity MAPK cascade components not only led to decreased cell wall integrity, but also decreased sclerotia formation and virulence (Bashi et al, 2016; Cong et al, 2022). In contrast, depending on the dysregulated pathway, S. sclerotiorum exhibited differing mycelial morphologies, suggesting that downstream components of the pheromone response, high osmolarity and cell wall integrity MAPK pathways likely function independently with some overlap (Li et al, 2021; Cong et al, 2022). However, the details of crosstalk among the three MAPK signaling pathways in regulating S. sclerotiorum development and virulence require further careful analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the histidine kinase deletion mutants showed increased sensitivity to osmotic and oxidative stresses. , The Hog1, which is the last kinase of the HOG pathway, is regulated by the histidine kinase and is associated with a stress response, morphology (e.g., sclerotia formation or hyphal growth), and virulence in Fusarium graminearum and Verticillium dahliae. , Based on the role of two-component histidine kinases, , it was suggested that Shk1 controls both SsOs4-SsOs5-SsHog1 cascade and SsSkn7 signaling pathways, which are involved in osmolar adaptation and fludioxonil sensitivity in S. sclerotiorum . The Ssos4 gene, which is the upstream kinase in the Hog1 MAPK pathway, is involved in mycelial growth, reduced virulence, hyperosmotic adaptation, and resistance to phenylpyrrole and dicarboximide fungicides .…”
Section: Introductionmentioning
confidence: 99%
“…sclerotiorum . The Ssos4 gene, which is the upstream kinase in the Hog1 MAPK pathway, is involved in mycelial growth, reduced virulence, hyperosmotic adaptation, and resistance to phenylpyrrole and dicarboximide fungicides . However, the function of S.…”
Section: Introductionmentioning
confidence: 99%